Standardization of screening technique for root rot disease (Macrophomina phaseolina) of castor: Standardization of screening technique for root rot disease (Macrophomina phaseolina) of castor - M SANTHA LAKSHMI PRASAD; T MANJUNATHA (Journal of Oilseeds Research, 2023)
Root rot caused by Macrophomina phaseolina is a major disease of castor in endemic areas and under water stress conditions. Sick pot method was found better artificial inoculation method for screening of castor genotypes than stem tape inoculation method and sorghum grown inoculum of M. phaseolina @ 35 g/kg soil standardized for sick pot method. In both inoculation methods, parental lines ICS-303, ICS-304, ICS-305, ICS-319, DPC-22, and IPC-46 recorded <10% root rot incidence, while ICS-298, ICS-312, and ICS-321 recorded <20% root rot incidence.